Dominica : Disaster Resilience Strategy. (IMF Staff Country Reports; Country Report ;, 2021)
Dominica is among the countries most vulnerable to natural disasters and climate change. During 1997-2017, it was the country with highest GDP losses to climate-related natural disasters and ranked in the top 10 percent among 182 countries for climate-related fatalities. Following a huge devastation, owing to back-to-back major storms in 2015 and 2017, Dominica announced its intention to become the first disaster resilient nation. In 2019, it was agreed with the government that the Fund, in consultation and collaboration with other development partners, would provide support for preparing a Disaster Resilience Strategy (DRS), a comprehensive plan including policies, cost, and financing to build resilience against natural disasters.